Parental involvement and its effects on satisfaction of parent-child relationship - Yeoh, Si Han *; Woo, Pei Jun * (Sunway University College, 2010)
Families and parenting have long been a research concern over the decades. However, little research has been conducted on the pattern(s) of parental involvement in the Malaysian context. Therefore, this study aims to investigate the effects of Malaysian young adults? perceived parental involvement on satisfaction of parent-child relationship. A questionnaire survey with Father Involvement Scale, Mother Involvement Scale, and Satisfaction of Parent-Child Relationship Scale was carried out on 100 male and 100 female local university and college students aged 18 to 25 years old. The findings show that father expressive and mentoring?advising involvement, and mother expressive involvement predict a better parent-child relationship. Overall, this study gives us a better understanding on the dimensions of Malaysian?s parental involvement that promotes better parent-child relationship.